Reverse coattail effects in undemocratic elections: an analysis of Russian locomotives. Issue 4 (7th June 2017) - Moraski, Bryon J.
ABSTRACT: This article argues that the effectiveness of the tactics ruling parties use to control the electoral arena may depend on the electoral experience of its subordinates. To substantiate this point, the work examines Russia's "locomotives" – the practice of placing regional governors on the list of the ruling party, United Russia, during national legislative elections. It argues that electoral payoffs also came from select regions without locomotives. Given the move to appointed governors, list exclusion likely indicated gubernatorial vulnerability. As a result, governors left off United Russia's list may have responded by seeking to demonstrate their electoral utility, and those with longer tenures were more likely to succeed in these efforts. An analysis of the 2007 Duma elections shows that United Russia's vote share was higher in regions where long-serving governors were left off the list. Since Russia's appointment system dramatically changed the gubernatorial corps between 2007 and 2011, the article also considers changes in the effects of list placement over time. It finds that the relationship between list exclusion and higher vote shares for United Russia disappears as governors with electoral experience were removed from office.